LEGISLATIVE ISSUES OF INVOLVING MILITARY EMPLOYEES IN THE MOBILIZATION MILITARY SERVICE - Harutyunyan, Hamlet (State and Law, 2023)
The article discusses the question of the scope of RA citizens who bear the legal obligation to be called up for mobilization military service in the context of the current legislative provisions, whether such an obligation is imposed on employees of various military agencies, including the police, the national security service, the penitentiary and rescue services. The relevance of this analysis is especially highlighted due to the fact that in September-November 2020, representatives of the above agencies took part in hostilities to repel the aggressive attacks committed by Azerbaijan against Artsakh and Armenia, to fulfill the duty of defending the motherland (in this case, of course, speech not about representatives of the police or border troops: the legal norms on the possibility of their participation in hostilities are specifically provided for and will also be presented in the article).